Econometric Analysis of Factors Influencing the Efficiency of Banking Services - Saidov, Jasur; Ibadullaev, Dilshad; Buranova, Lola; Tuychieva, Madina; Melibayeva, Gulkhon; Makhmudov, Samariddin; Mamadiyarov, Zokir (International Journal of Economics and Financial Issues, 2025)
As a result of increasing the efficiency of banking services, the possibility of increasing competitiveness, full satisfaction of customer needs and profitability increases. This article examines various strategies and effects that can be used to optimize banking services. In addition, the article analyzes factors that affect the increase in interest income of Agrobank JSCB, such as the volume of Agrobank JSCB's assets, the volume of remote banking services provided by Agrobank JSCB, the inflation rate, the ROE coefficient of Agrobank JSCB, and ways to reduce operating costs. As a result, a 1% increase in the volume of assets of Agrobank JSCB will increase the bank's profit margin by 0.50%, a 1% increase in remote banking services of Agrobank JSCB will increase the bank's profit margin by 1.25%, and a 1% increase in the inflation rate will reduce the bank's profit margin by 0.98%. Also, a 1% increase in the return on equity (ROE) of Agrobank JSCB will increase the bank's profit margin by 0.50%. It should be noted that banks that invest in these areas can achieve a significant increase in operational efficiency and overall financial indicators in providing services. In the study, the multiple linear regression (LS) model demonstrates that the fusion of factors such as the asset volume of "Agrobank" JSCB, the volume of remote banking services, the return on equity (ROE) coefficient, and the inflation rate has a positive relationship with the bank's total interest income. The integrated impact of these variables contributes significantly to the improvement of the bank’s financial performance indicators.